Circulating tumor cells in peripheral blood of pancreatic cancer patients and their prognostic role: a systematic review and meta-analysis. Issue 5 (May 2020) - Wang, Yang; Yu, Xiaojin; Hartmann, Daniel; Zhou, Jiahua
Abstract: Background: It has been shown that circulating tumor cells in peripheral blood can be used to predict survival in patients with breast, prostate and other epithelial tumors. In the present study, we performed a meta-analysis to evaluate the prognostic role of circulating tumor cells (CTCs) in patients with pancreatic cancer. Methods: A systematic literature search of the databases was conducted from the inception to Jul 20, 2019. Relative risks (RRs) with 95% confidence intervals (CIs) were calculated under a fixed or random effect model. Results: A total of 19 studies with 1320 confirmed individuals were included. Our meta-analysis showed that patients in the CTC-positive group had a significantly shorter overall survival (OS) (RR = 0.47, 95%CI = 0.33–0.61, P < 0.001) and progression-free survival (PFS) (P = 0.003) than CTC-negative patients. Moreover, subgroup analysis by ethnicity indicated that CTC-positive patients had a significantly shorter OS in both Asian and Western populations. Further subgroup analysis by detection methods, treatments, and Tumor Node Metastasis (TNM) stages also indicated that CTC-positive patients were associated with significant decreases in both OS and PFS  in most subgroups. Conclusion: Our meta-analysis indicates that CTC-positive patients have a worse OS and PFS than CTC-negative patients, which suggests that CTCs may act as predictive biomarkers for pancreatic cancer patients before treatment.